2001
DOI: 10.1037/0021-843x.110.3.488
|View full text |Cite
|
Sign up to set email alerts
|

Diminished response to pleasant stimuli by depressed women.

Abstract: This study examined the self-report and facial expressions of emotional response to pictorial stimuli and the incidental learning of pleasant and unpleasant words by depressed (n = 20) and nondepressed (n = 20) women. Depression was associated with reports of diminished emotional response and reduced frequency and intensity of facial expressions only to pleasant stimuli. The 2 groups did not differ in response to hedonically unpleasant stimuli, even those specifically relevant to the emotion of sadness. In a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
173
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 195 publications
(210 citation statements)
references
References 28 publications
(32 reference statements)
31
173
3
3
Order By: Relevance
“…The findings emerging from the present study are consistent with and extend prior reports in depression of reduced reactivity to pleasant cues (e.g., Sloan et al, 2001;Suslow et al, 2001), blunted reward responsiveness (e.g., Henriques and Davidson, 2000), and diminished attentional positivity bias (e.g., McCabe and Gotlib, 1995;Wang et al, 2006). Unlike prior studies, however, the current work provides initial evidence that clinically depressed subjects show a diminished propensity to modulate behavior as a function of reinforcement history, particularly in the absence of immediate reinforcement.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The findings emerging from the present study are consistent with and extend prior reports in depression of reduced reactivity to pleasant cues (e.g., Sloan et al, 2001;Suslow et al, 2001), blunted reward responsiveness (e.g., Henriques and Davidson, 2000), and diminished attentional positivity bias (e.g., McCabe and Gotlib, 1995;Wang et al, 2006). Unlike prior studies, however, the current work provides initial evidence that clinically depressed subjects show a diminished propensity to modulate behavior as a function of reinforcement history, particularly in the absence of immediate reinforcement.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, resting activity within left prefrontal regions has been linked to individuals' propensity to respond to rewardrelated cues , providing convergent evidence that depressed subjects might display reduced hedonic capacity. Finally, studies employing various paradigms have shown that depressed subjects display a blunted emotional response to pleasant cues (e.g., Sloan et al, 2001;Suslow et al, 2001), decreased reward responsiveness (e.g., Henriques and Davidson, 2000), a lack of a positivity bias in attentional tasks (e.g., McCabe and Gotlib, 1995;Wang et al, 2006), and dysfunctions within the brain reward system (e.g., Keedwell et al, 2005;Tremblay et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in comparison to nondepressed participants, individuals with clinical and subclinical depression do not show an increased activity of the zygomaticus major muscle in response to happy expressions (Sloan et al, 2002), pleasant images (Sloan et al, 2001), and happy imagery (Schwartz et al, 1976). Based on these findings, we expect that there are normal affective responses to negative events but reduced affective responses to positive events in depression.…”
Section: Reward and Punishment Consumption From A Facial Expressions mentioning
confidence: 80%
“…The few studies that focus on facial EMG activity in depression demonstrate that individuals with clinical and subclinical depression respond with increased activity of the corrugator supercilii muscle to unhappy expressions (Sloan, Bradley, Dimoulas, & Lang, 2002), unpleasant images (Sloan, Strauss, & Wisner, 2001), and sad imagery (Schwartz, Fair, Salt, Mandel, & Klerman, 1976), just as do nondepressed control participants. However, in comparison to nondepressed participants, individuals with clinical and subclinical depression do not show an increased activity of the zygomaticus major muscle in response to happy expressions (Sloan et al, 2002), pleasant images (Sloan et al, 2001), and happy imagery (Schwartz et al, 1976).…”
Section: Reward and Punishment Consumption From A Facial Expressions mentioning
confidence: 99%